A CPW‐fed triple band OCSRR embedded monopole antenna with modified ground for WLAN and WIMAX applications. Issue 10 (October 2015) - Pandeeswari, R.; Raghavan, S.
ABSTRACT A coplanar waveguide fed triple band antenna is proposed for wireless local area network (WLAN) and worldwide interoperability for microwave access (WIMAX) applications. The proposed antenna consists of rectangle monopole with modified ground plane and open complementary split ring resonator (OCSRR) loading. The overall size of the antenna is 30 × 40 × 0.8 mm3, which provides Omnidirectional pattern in all three bands. The prototype of antenna is designed, fabricated, and measured. The measured −10 dB impedance bandwidths are 300 MHz (2.40–2.70 GHz), 680 MHz (3.32–4.00 GHz), and 1040 MHz (4.76–5.8 GHz) with resonance frequency at 2.6 GHz, 3.4GHz, and 5GHz, respectively, which is suitable for WLAN/WiMAX applications. Parametric study on OCSRR is discussed to validate the results. Simulated and measured results of the antenna are presented and discussed. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:2413–2418, 2015